Implementation of Patient Complaint Management Mechanisms for Quality Improvement in Maternal Health Services: Exploration of Provider Perspectives at Mkuranga District Hospital - August F; Nyamhanga T; Kakoko DC; Anaeli A; Mwangu MA (International Journal of Women's Health)
Francis August,1 Tumaini Nyamhanga,1 Deodatus Conatus Kakoko,2 Amani Anaeli,1 Mughwira Ally Mwangu1 1Department of Development Studies, School of Public Health and Social Sciences, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 2Department of Behavioural Sciences, School of Public Health and Social Sciences, Muhimbili University of Health and Allied Sciences, Dar es Salaam, TanzaniaCorrespondence: Francis August, Department of Development Studies, School of Public Health and Social Sciences, Muhimbili University of Health and Allied Sciences, Tanzania, 9 United Nations Road Upanga West, Dar es Salaam, P.O. Box 65454, Tanzania, Email francisaugust6@gmail.comBackground: Although patient complaints are stressful, they are regarded as useful when framed as learning avenues (ie checks and balances in service delivery), further contributing to quality improvement mechanisms and enhancing accountability. A well-structured system of receiving and managing complaints may result in, but is not limited to, improved accountability, control of abuse and vulgar language, and assurance/compliance with the code of conduct or procedure. Tanzania established a National Guide for Complaint Management in Health Facilities. It is a prerequisite in Health facilities to enable to use of evidence from the complaints process for quality improvement. Despite the emphasis on feedback from patient concerns and the availability of a guide for patient concern management in Tanzania, there is a paucity of information on how well patients’ complaints are received, dealt with, and managed by district hospitals, especially those emerging from maternal, newborn, and child health services.Objective: This study aimed to assess providers’ perspectives on the implementation of Tanzania’s guidelines for managing patient concerns in service delivery.Methods: A qualitative approach was used for data collection, and content analysis was performed.Results: The findings underscore the challenges related to hospital infrastructure for receiving patients’ complaints, ie awareness and enthusiasm to use them, how complaints are dealt with, ie processing of the complaints, feedback mechanisms, ie learning from the complaints, integrating lessons learned from the complaints into service delivery, and quality improvement mechanisms in maternal health services. Findings are framed as barriers and facilitators of the process of receiving complaints and processing complaints/concerns, together with feedback mechanisms.Conclusion: The implementation of patient complaint mechanisms has remained ineffective despite the reported enablers, which smooth the implementation of patients’ complaints, such as the availability of structures and guidelines, citizens’ engagement/participation, self-esteem, and enthusiasm.Keywords: patient complaints, quality improvement, maternal health, accountability mechanisms